2003
DOI: 10.1061/(asce)0733-9445(2003)129:2(253)
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strength and Fiber Reinforcement on Fire Resistance of High-Strength Concrete Columns

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(111 citation statements)
references
References 3 publications
5
93
0
2
Order By: Relevance
“…Based on detailed experimental studies on HSC columns, it was found that spalling occurs when temperatures in concrete reach above 350°C [7]. This is shown in Figure 3, which shows temperatures at various time intervals and the initiation of spalling, as observed during fire resistance test of column THC4.…”
Section: Extent Of Spallingmentioning
confidence: 96%
See 3 more Smart Citations
“…Based on detailed experimental studies on HSC columns, it was found that spalling occurs when temperatures in concrete reach above 350°C [7]. This is shown in Figure 3, which shows temperatures at various time intervals and the initiation of spalling, as observed during fire resistance test of column THC4.…”
Section: Extent Of Spallingmentioning
confidence: 96%
“…Further, the presence of steel or polypropylene fibers and the type of aggregate in concrete influence the extent of spalling [7]. The spalling was highest in column THC4 which was made with siliceous aggregate.…”
Section: Fire Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Han et al [8] performed an experimental fire performance study of concrete-filled stainless steel tube columns directed toward off-shore structural applications. Kodur et al, has conducted several studies on the effects of fiber reinforcement, fly ash, and tie configuration on the fire performance of high-strength concrete (HSC) columns [9][10][11][12]. There have also been a significant number of studies conducted on fiber reinforced polymer (FRP) confined concrete columns, including those conducted by Green et al [13], Chowdury et al [14], Cree et al [15], Gefu et al [16], Bisby et al [17] and Kodur et al [18] to name a few.…”
Section: Open Accessmentioning
confidence: 99%